2019
DOI: 10.1103/physrevresearch.1.033131
|View full text |Cite
|
Sign up to set email alerts
|

Origins versus fingerprints of the Jahn-Teller effect in d -electron ABX3 perovskites

Abstract: The Jahn-Teller (JT) distortion that can remove electronic degeneracies in partially occupied states and results in systematic atomic displacements is a common underlying feature to many of the intriguing phenomena observed in 3d perovskites, encompassing magnetism, superconductivity, orbital ordering and colossal magnetoresistance. Although the seminal Jahn and Teller theorem has been postulated almost a century ago, the origins of this effect in perovskite materials are still debated, including propositions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Overall the observed magnetisation is much lower than 1 µ B /Ta as expected from the simplest paramagnetic model. The small magnetic moment and the fact that Ta is a 5d element suggests that the largely extended 5d orbitals in LaTaO 2 N are strongly hybridised and overlapping with the O/N 2p orbitals 30 leading to weakly localised electrons hampering the up-built of a significant magnetisation. It is wellknown for 3d transition metal containing perovskites ABO 3 and ABF 3 that with decreasing electronegativity of the anion the hybridisation (or in other words the covalency of the B-X bond) is enhanced resulting in the aforementioned stronger delocalisation of the electrons and hence the spin 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall the observed magnetisation is much lower than 1 µ B /Ta as expected from the simplest paramagnetic model. The small magnetic moment and the fact that Ta is a 5d element suggests that the largely extended 5d orbitals in LaTaO 2 N are strongly hybridised and overlapping with the O/N 2p orbitals 30 leading to weakly localised electrons hampering the up-built of a significant magnetisation. It is wellknown for 3d transition metal containing perovskites ABO 3 and ABF 3 that with decreasing electronegativity of the anion the hybridisation (or in other words the covalency of the B-X bond) is enhanced resulting in the aforementioned stronger delocalisation of the electrons and hence the spin 30 .…”
Section: Resultsmentioning
confidence: 99%
“…5b). The band gap opening mechanism has been recently explained by Varignon et al 46 , who demonstrated that the ground state LaMnO3 insulator structure has pseudo-Jahn-Teller distortion -the 𝑄 2 + octahedral deformation is a consequence of pure semiclassical atomic size effects resulting in octahedral rotations/tilts and not induced by an electronic instability, which is the origin of true Jahn-Teller distortion. + distortion results in an insulator.…”
Section: Gapping Due To Allowance Of Jahn-teller-like Distortionmentioning
confidence: 95%
“…2). 27,[41][42][43][44][45][46][47][48][49][50][51][52][53] As the exclusive allure of "correlated materials" is diminishing, it has become more pragmatic to refer to interesting materials as "quantum materials" whether they are correlated or not. This changed material focus is no longer restricted to compounds containing "correlation agents" such as open-shell d-or f-electron elements but now has a different sort of structural and spin-orbit complexity that adds interesting doping challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The observed positional symmetry breaking in LaMnO3 is a pseudo Jahn-Teller distortion, leading to inequivalent Mn-O bond lengths in (MnO6) octahedron. It has been recently shown [71] that distortions that originate from the energy lowering associated with degeneracy removal (i.e., electronic instability such as this work with results reported in DMFT reference [44]), and comparable to experimental observation of 𝛽 ℎ =2.6-2.8 in La0.6Sr0.4MnO3 [52]. We conclude that pseudo Jahn-Teller distortion 𝑄 2 + captured by mean-field DFT is capable of producing significant mass renormalizations, even though on this case both DFT and DMFT give smaller renormalization than what was measured, which may be due to the A-site alloy effect in the measured sample La0.6Sr0.4MnO3 [52].…”
Section: B Jahn-teller-like 𝑸 𝟐 + Distortion Enhances Masses In Lamno3mentioning
confidence: 97%